“We are dragged along like dogs and take damage …” – Adolescents’ experiences affecting their mental health during vocational training in a health or social care profession – an interpretative phenomenological analysis - Katja Weidling; David Spoerlé; Flavio Mariano Heller; Manuel P. Stadtmann (BMC Public Health)
Abstract Background The foundation for mental health is laid in childhood and adolescence. For young people, adolescence is associated with multiple developmental tasks. In this vulnerable phase of life, they often start a vocational training. Particularly during vocational training in the health and social care sector, adolescents are confronted with highly stressful situations, e.g., serious illness, death, or sexual harassment. In this study we aimed to explore adolescents’ experiences and perceptions affecting their mental health during vocational education and training. Methods We performed five focus group interviews with a total of 41 vocational education and training students from different fields in the health and social care professions. Data analysis was based on Interpretative Phenomenological Analysis (IPA) according to Smith. Results We identified five superordinate themes and 17 subordinate themes. The personal circumstances and the pronounced shortage of staff throughout the health and social care sector play a major role for the vocational education and training students’ (VETs) mental health during their vocational training. In addition, vocational education and training students are confronted with various challenges that are atypical for their age (e.g. the death of a patient). They try to being able to maintain a balance between the stressful factors and the coping strategies available to them. This can improve as well as worsen mental health and well-being. Vocational education and training students express the need to counteract the stressful factors of their vocational training with positive aspects of their lives. They try to find a bridge to the outside world again. However, they depend on the support from the vocational training school, the vocational training company, and their social environment. Conclusion Today’s vocational education and training students are tomorrow’s skilled workers. Investing in their mental health can help reduce staff shortages in the long term and prevent mental health impairments in this vulnerable group. To this end, training institutions, companies and politicians should create appropriate framework conditions.